Demand forecasting for supply processes in consideration of pricing and market information - Reiner, Gerald; Fichtinger, Johannes (Elsevier Science B.V., Amsterdam., 2009)
We develop a dynamic model that can be used to evaluate supply chain process improvements, e.g. different forecast methods. In particular we use for evaluation a bullwhip effect measure, the service level (fill rate) and the average on hold inventory. We define and apply a robustness criterion to enable the comparison of different process alternatives, i.e. the range of observation periods above a certain service level. This criterion can help managers to reduce risks and furthermore variability by applying robust process improvements. Furthermore we are able to demonstrate with our research results that the bullwhip effect is an important but not the only performance measure that should be used to evaluate process improvements.